Defect Mediated Small Molecular Doping of Graphene. Issue 14 (2nd February 2021) - S, Ragul; Dutta, Soumya; Ray, Debdutta
Abstract: It is shown that the improved electrical properties of graphene on organic small‐molecule‐based surface doping is dominated by the doping effect of these materials at the defect sites on graphene. It is hypothesized that this may be due to the healing effect of semi‐bulk substitution‐like doping at the defect sites. In this study, defects are intentionally created with varying densities on graphene by exposing it to trifluoro methane (CHF3 ) plasma for different time periods. The films are then doped by solution spin coating of bis(trifluoromethane)sulfonamide (TFSA). The measured change in electrical conductivity is proportional to the defect density of the graphene, implying a healing effect of these organic small molecular dopants. First principles calculations are performed to capture this mechanism, and the results conform with the experimental observations. The introduction of defects leads to a modulation of the workfunction while adversely affecting the charge carrier transport properties. It is shown that subsequent TFSA doping aids in healing the defective sites thereby improving conduction while maintaining the changed workfunction. The two processes act in tandem for the enhanced electrical properties of graphene. Abstract : The modulation of the electrical properties of graphene through incorporation of organic dopants at defect sites is investigated. Artificial defect generation by fluorine plasma tends to increase the workfunction but decrease the conductivity. The dopant functionalization leads to a healing effect at the defect sites thereby leading to an improvement in the electrical transport properties.